Effects of grazing on growth and morphology of rhizomatous and caespitose grasses in tallgrass prairie - N'Guessan, Maipelo (Kansas State University, 2007)
Herbivory is one of the major biotic interactions shaping the structure and dynamics of grassland plant populations and community structure. The two major grass growth forms, rhizomatous and caespitose species, may show different grazing tolerance and short-term overcompensation may offset long-term reductions in plant performance and fitness. The objectives of this study were to assess 1) the effects of long-term ungulate grazing on plant architecture, population structure, and life history traits of the caespitose perennial grass, Schizachyrium scoparium (little bluestem), and the rhizomatous Bouteloua curtipendula (sideoats grama) in tallgrass prairie, and 2) the effects of grazing intensity (frequency of defoliation) on growth responses of little bluestem. Long-term bison grazing decreased the cover, frequency, tiller height, and proportion of tillers producing seed in little bluestem, but caused no changes in tiller density and total genet size. Grazed little bluestem plants maintained a significantly larger below ground bud bank. Bison grazing had no long-term effect on the abundance, bud bank densities, or rhizome growth of the rhizomatous side-oats grama grass. Biomass, tiller density, relative growth rates, and proportion of tillers flowering in little bluestem all decreased with increasing frequency of defoliation. However, even an intense grazing regime (9 defoliations over a 12 month period) caused no plant mortality and no changes in new tiller emergence rates, or bud bank densities. Increasing defoliation frequency did result in shifts in plant architecture, as an increasing proportion of extravaginal tillers led to a more lateral, decumbent growth form. These results show that the rhizomatous side-oats grama grass has a significantly higher grazing tolerance than does little bluestem, and/or that bison selectively graze little bluestem. Results from responses to the experimental defoliation regimes suggest that little bluestem shows lower tolerance to high frequency of defoliation, and its maintenance of a reserve below ground bud bank may be its primary tolerance mechanism, allowing tiller populations to recover following severe defoliation.
Keywords: grazing; growth; caespitose; rhizomatous; morphology; tallgrass; Biology, Ecology (0329)